2016
DOI: 10.1186/s12937-016-0206-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of imposed exercise on energy intake in children at risk for overweight

Abstract: BackgroundExercise not only has a direct effect on energy balance through energy expenditure (EE), but also has an indirect effect through its impact on energy intake (EI). This study examined the effects of acute exercise on daily ad libitum EI in children at risk for becoming overweight due to family history.MethodsTwenty healthy-weight children (ages 9–12 years, 12 male/8 female) with at least one overweight biological parent (body mass index ≥ 25 kg/m2) participated. Children reported to the laboratory for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 51 publications
(53 reference statements)
2
16
0
2
Order By: Relevance
“…Although in their study questioning the impact of an acute intensive cycling bout (70% V̇O 2max ) among pre‐pubertal children at risk for overweight/obesity (defined as having at least one parent with obesity), Fearnbach and collaborators did not find any subsequent differences in EI compared with a non‐exercise control day. In this study, FFM index (FFM (kg) /height (m 2 )) was positively associated with EI on the exercise but not the control day, suggesting a better homeostatic EI regulation with imposed exercise in this sample . This is particularly interesting since the homeostatic regulation of energy balance is not limited to the metabolic changes associated with EE fluctuations and that body composition has been shown to be involved in the regulation of EI, FFM being a good predictor of EI (better than FM) in both adolescents and adults .…”
Section: Does Appetite Change In Response To Acute Exercise In Lean Cmentioning
confidence: 56%
“…Although in their study questioning the impact of an acute intensive cycling bout (70% V̇O 2max ) among pre‐pubertal children at risk for overweight/obesity (defined as having at least one parent with obesity), Fearnbach and collaborators did not find any subsequent differences in EI compared with a non‐exercise control day. In this study, FFM index (FFM (kg) /height (m 2 )) was positively associated with EI on the exercise but not the control day, suggesting a better homeostatic EI regulation with imposed exercise in this sample . This is particularly interesting since the homeostatic regulation of energy balance is not limited to the metabolic changes associated with EE fluctuations and that body composition has been shown to be involved in the regulation of EI, FFM being a good predictor of EI (better than FM) in both adolescents and adults .…”
Section: Does Appetite Change In Response To Acute Exercise In Lean Cmentioning
confidence: 56%
“…The relationship between exercise and neural response to food pictures has also recently been investigated in adolescents using event-related potentials (ERPs) to demonstrate that food stimuli resulted in lower neural activation (i.e., decreased amplitude of the P3b ERP component) following exercise compared to non-food stimuli (Fearnbach et al 2016). The difference in neural activity between food and non-food stimuli was not present following sedentary activity (Fearnbach et al 2016). However, the extent to which the relationship between the brain response to food-related stimuli and exercise exists in children is not yet known.…”
Section: Introductionmentioning
confidence: 99%
“…While not specially designed and focused on the effect of the exercise-timing, results from studies using similar exercises and conducted among similar populations tend to suggest potentially different energy intake responses depending on the delay between exercise and the subsequent meal. In their work, Fearnbach et al for instance showed reduced ad libitum energy intake in 12-15 years old adolescents with obesity 30 minutes after an acute bout of moderate intensity cycling exercise [34,35] while others failed to observe any food consumption modification in a similar population when the same exercise is performed 60 minutes before lunch [36].…”
Section: The Exercise-meal Delaymentioning
confidence: 99%